Circulating syndecan-1 is reduced in pregnancies with poor fetal growth and its secretion regulated by matrix metalloproteinases and the mitochondria - Damanpreet Garcha (Nature Portfolio, 2021)
Abstract Fetal growth restriction is a leading cause of stillbirth that often remains undetected during pregnancy. Identifying novel biomarkers may improve detection of pregnancies at risk. This study aimed to assess syndecan-1 as a biomarker for small for gestational age (SGA) or fetal growth restricted (FGR) pregnancies and determine its molecular regulation. Circulating maternal syndecan-1 was measured in several cohorts; a large prospective cohort collected around 36 weeks’ gestation (n = 1206), a case control study from the Manchester Antenatal Vascular service (285 women sampled at 24–34 weeks’ gestation); two prospective cohorts collected on the day of delivery (36 + 3–41 + 3 weeks’ gestation, n = 562 and n = 405 respectively) and a cohort who delivered for preterm FGR (< 34 weeks). Circulating syndecan-1 was consistently reduced in women destined to deliver growth restricted infants and those delivering for preterm disease. Syndecan-1 secretion was reduced by hypoxia, and its loss impaired proliferation. Matrix metalloproteinases and mitochondrial electron transport chain inhibitors significantly reduced syndecan-1 secretion, an effect that was rescued by coadministration of succinate, a mitochondrial electron transport chain activator. In conclusion, circulating syndecan-1 is reduced among cases of term and preterm growth restriction and has potential for inclusion in multi-marker algorithms to improve detection of poorly grown fetuses.